Teknologi Informasi Berbasis XBRL Dan Potensi Peningkatan Kualitas Pengungkapan - Hendra Tanjung (JAS (Jurnal Akuntansi Syariah), 2021)
Various countries globally have widely used eXtensible Business Reporting Language (XBRL) technology for the financial reporting of public companies. However, studies on the sophistication of XBRL technology and its potential for improving the quality of disclosure have not been widely reviewed. This paper examines this matter with the literature review method, and conclusions are prepared based on qualitative analysis. The XBRL-based reporting system has many advantages compared to the previous reporting system, including faster data transfer, efficiency, and others. In addition, the tag system in XBRL allows users to know more details about the information conveyed. The tag system allows users to search for relevant information and easily compare with different companies. Therefore, the management practice of disclosing financial statements and financial statements is presented explicitly to users of financial statements. Thus, the sophistication of a reporting system based on information technology XBRL can increase transparency and better disclosure.